(untitled) (Journal of the Management Sciences, 2023)
Adequate financing of the agricultural sector is imperative for a robust food security programme and poverty reduction initiatives. This study examined effect of financial intermediation on agricultural production among members of cooperative societies in Anambra State. The objectives are to examine the influence of cost of credit on agricultural production among members of cooperative societies in Anambra State; to determine the influence of amount of credit borrowed on agricultural production among the cooperative societies in Anambra State; to assess the effect of credit repayment on agricultural production among the cooperative societies in Anambra State. The study adopted a descriptive survey research design that aimed to determine the relationship between the independent variables and dependent variable in a population. The population of this study was made up of members of registered Famers Multipurpose Cooperative Societies with membership strength of 6986. A sample of 287 was determined for the study using Taro Yamane formula after the multi-stage sampling technique was used. A structured questionnaire was administered to 287 respondents but only 266 responded to the questionnaire. The hypotheses of the study showed that the five coefficients of credit (socioeconomic characteristics, Cost of cooperative credit, Amount of Credit Borrowed, Loan repayment period and Loan Repayment Performance) significantly influenced agricultural production among members’ cooperative societies in Anambra State at 5% significant levels. The study recommends that young and able bodied men and women particularly new graduates without employment should embrace agricultural production. This will help reduce poverty, unemployment, increase food output and help them build career in the agricultural sector. In order to address the challenge of cost of cooperative credit, credit institutions should ensure that loans are given on time. The repayment period for credit obtained should be spread in such a way that the cost will not be heavy on the farmers. Agricultural credit lending institutions should provide adequate credit facilities to cooperative farmers to enable them increase their production capacity among others.